China : Sources of Real Exchange Rate Fluctuations - Wang, Tao (IMF Working Papers; Working Paper ;, 2004)
This paper reviews the evolution of China's real effective exchange rate between 1980 and 2002, and uses a structural vector autoregression model to study the relative importance of different types of macroeconomic shocks for fluctuations in the real exchange rate. The structural decomposition shows that relative real demand and supply shocks account for most of the variations in real exchange rate changes during the estimation period. The paper also finds that supply shocks are as important as nominal shocks in accounting for real exchange rate fluctuations, in contrast with other studies that show that, in industrial countries, nominal shocks are more important in explaining real exchange rate fluctuations.